2023
DOI: 10.3390/aerospace10060499
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Nitrogen Flow Boiling Critical Heat Flux in Additively Manufactured Cooling Channels

Abstract: This paper presents an experimental characterization of liquid nitrogen (LN2) flow boiling in additively manufactured minichannels. There is a pressing need of concerted efforts from the space exploration and thermal transport communities to design high-performance rocket engine cooling channels. A close observation of the literature gaps warrants a systematic cryogenic flow boiling characterization of asymmetrically heated small (<3 mm) non-circular channels fabricated with advanced manufacturing technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In this context, Ortega et al [22] reported the results of liquid nitrogen flow boiling for asymmetrically heated GR-Cop42 channels. The experiments were conducted at different mass flux pressures and subcooling degrees.…”
Section: Flow Boilingmentioning
confidence: 99%
“…In this context, Ortega et al [22] reported the results of liquid nitrogen flow boiling for asymmetrically heated GR-Cop42 channels. The experiments were conducted at different mass flux pressures and subcooling degrees.…”
Section: Flow Boilingmentioning
confidence: 99%